The Effects of Exercise on Abdominal Fat and Liver Enzymes in Pediatric Obesity: A Systematic Review and Meta-Analysis - Garcia-Hermoso, A (Mary Ann Liebert Inc., 2017)
Background: Despite the prevalence of obesity and the multiple position stands promoting exercise for the treatment of obesity and hepatic function, a meta-analytic approach has not previously been used to examine the effects in the pediatric population. The aim of the study was to determine the effectiveness of exercise interventions on abdominal fat, liver enzymes, and intrahepatic fat in overweight and obese youth. Materials and Methods: A computerized search was made using three databases. The analysis was restricted to studies that examined the effect of supervised exercise interventions on abdominal fat (visceral and subcutaneous fat), liver enzymes (alanine aminotransferase, aspartate aminotransferase, and gamma-glutamyl transferase), and intrahepatic fat. Fourteen clinical trials (1231 youths) were eligible for inclusion in this systematic review and meta-analysis. Standardized mean difference [SMD] and 95% confidence intervals (CIs) were calculated. Results: Exercise was associated with a significant reduction in visceral (SMD = -0.661; 95% CI, -0.976 to -0.346; p < 0.001), subcutaneous (SMD = -0.352; 95% CI, -0.517 to -0.186; p < 0.001) and intrahepatic fat (SMD = -0.802; 95% CI, -1.124 to -0.480; p < 0.001), as well as gamma-glutamyl transferase (SMD = -0.726; 95% CI, -1.203 to -0.249; p < 0.001), but did not alter any other liver enzyme. Subgroup analysis recommends exercise programs that involve aerobic exercise longer than three sessions per week. Conclusions: This meta-analysis supports current recommendation for physical exercise, mainly aerobic, as an effective intervention for nonalcoholic fatty liver disease progression by targeting hepatic lipid composition, visceral and subcutaneous adipose tissue. Systematic review registration: PROSPERO CRD42016042163. © Copyright 2017, Mary Ann Liebert, Inc..